Spare the rod or spoil the eye? corporal punishment- related eye injuries among children presenting to tertiary hospital in South West Nigeria (2018)
Objective: To determine the burden of corporal punishment in the aetiology of ocular injuries among children, to inform evidence-based advocacy measures to curb this trend. Methodology: This study was a retrospective review of cases of punishment-related ocular injuries among children aged 16 years and less who presented to the Eye Emergency of the University College Hospital, Ibadan, between 2010 and 2016. Data on proportion of paediatric ocular trauma due to corporal punishment, patient demography, circumstance surrounding, and nature of injury, management and visual outcome were descriptively summarised. Results: There were 109 cases of paediatric eye injuries during the study period of which 18(16.5%) were due to corporal punishment. The mean age was 10.3 years (SD 2.7). Males comprised 61.1 % (11) of cases. Place of injury was at school in 10 (55.6%) and at home in 8 (44.4%) cases. All injuries were unilateral. Sixteen (88.9%) of these injuries were of the closed globe type and management was conservative in 15 (83.3%) children. Twelve (66.7%) children had visual acuity less than 3/60 at presentation while 8 (44.4%) had 6/18 or better vision as at time of last follow up. Conclusion: Punishment-related eye injuries are important in the aetiology of paediatric ocular trauma in our locality especially as relates to poor visual outcome. There is therefore the need for targeted sensitization of parents, care givers and teachers, as well as creation of awareness of alternative methods to corporal punishment and legislation in order to effectively tackle this problem.